A taxonomic review of the polymorphic assassin bug genus Rihirbus Stål (Hemiptera: Reduviidae: Harpactorinae) - Gao, Feng; Zhao, Ping; Webb, Mick; Cai, Wanzhi (Zootaxa, 2015)
Two species in the genus Rihirbus Stål are recognized, redescribed and illustrated. The diagnosis of the genus is slightly modified. The deposition information of Miller’s type specimens is corrected. Rihirbus trochantericus Stål is newly recorded from Cambodia, Laos, Nepal, Thailand, and Vietnam. A key for the identification of species of Rihirbus is provided. The sexual dimorphism and polymorphism of this genus are briefly noted.